Immune response to Haemonchus contortus and Haemonchus placei in sheep and its role on parasite specificity - Santos, Michelle C. [UNESP]; Xavier, Jorge K. [UNESP]; Amarante, Monica R. V. [UNESP]; Bassetto, Cesar C. [UNESP]; Amarante, Alessandro F. T. [UNESP] (Elsevier B.V., 2014)
Two trials were conducted to determine the prepatent and the patent period of Haemonchus contortus and Haemonchus placei in Santa Ines crossbred sheep and to determine whether serial infections with both species confer protection against homologous or heterologous challenge. To evaluate the prepatent and patent periods of infection, five lambs received a single infection with 4000 H. contortus-infective larvae (L3), and another five received a single infection with 4000 H. placei L3. H. contortus presented patency earlier than H. placei. Animals infected with both species shed a large number of eggs in the faeces for several months with the highest counts, with means higher than 3000 eggs per gram of faeces (EPG) between 24 and 106 days and between 38 and 73 days post infection with H. contortus and H. placei, respectively. H. contortus eggs were detected in the faeces for a minimum of 302 days and a maximum of 538 days post infection, while the H. placei patent period lasted from 288 to 364 days. In the second trial, one group of lambs (n = 12) was serially infected 12 times (three times per week for four weeks) with 500 L3 of H. placei and then challenged with either H. placei (n = 6) or with H. contortus (n = 6). The lambs in the second group (n = 12) were serially infected 12 times with 500 L3 of H. contortus and then challenged with H. contortus (n = 6) or with H. placei (n = 6), and a third group of lambs was single challenged with H. placei (n = 6), H. contortus (n = 6), or remained uninfected throughout the trial period (control group, n = 6). Animals serially infected with H. placei and then challenged with the same species presented the most intense immune response with the highest levels of antiparasitic immunoglobulin and number of inflammatory cells in the abomasal mucosa. As a result, this group had the lowest rate of parasite establishment (2.68% of the 4000 L3 given), but this phenomenon did not occur in animals single challenged with H. placei, in which the rate of establishment was relatively high (25.3%), confirming that the protective immune response to H. placei develops only when animals are repeatedly infected with this species. However, when the animals were previously serially infected with H. placei and then challenged with H. contortus, no evidence of significant protection was observed (establishment of 19.18%). The results of the trials showed an important role played by the immune response on parasite host specificity. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Epidemiology; Infection; Inflammatory cells; Nematode; Resistance; Ruminant